2019
DOI: 10.1111/jgs.16044
|View full text |Cite
|
Sign up to set email alerts
|

Serious Illness and End‐of‐Life Treatments for Nurses Compared with the General Population

Abstract: OBJECTIVES As key team members caring for people with advanced illness, nurses teach patients and families about managing their illnesses and help them to understand their options. Our objective was to determine if nurses' personal healthcare experience with serious illness and end‐of‐life (EOL) care differs from the general population as was shown for physicians. DESIGN Observational propensity‐matched cohort study. SETTING Fee‐for‐service Medicare. PARTICIPANTS Nurses' Health Study (NHS) and a random 20% nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In this issue, Bynum et al cleverly link the Nurses' Health Study (NHS), a cohort study with a population of over 120 000 female nurses with 42 years of followup, to the Medicare claims data to explore utilization patterns among people with Alzheimer dementia and related disorders (ADRDs) and heart failure (HF). 6 In sum, their findings were consistent with prior studies (ie, nurses and nonnurses use healthcare similarly).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In this issue, Bynum et al cleverly link the Nurses' Health Study (NHS), a cohort study with a population of over 120 000 female nurses with 42 years of followup, to the Medicare claims data to explore utilization patterns among people with Alzheimer dementia and related disorders (ADRDs) and heart failure (HF). 6 In sum, their findings were consistent with prior studies (ie, nurses and nonnurses use healthcare similarly).…”
supporting
confidence: 88%
“…Yet, the differences Bynum et al found between the nurse cohort and the nonnurse cohort for the outcomes of invasive interventions, death in the hospital, intensive care unit stay during terminal hospitalization, and hospice use only ranged from 2% to 4%. Unquestionably, the differences in end‐of‐life care patterns are statistically significant and clinically meaningful, but they are unremarkable.…”
mentioning
confidence: 99%